(untitled) - Scieszka, Jon.; Smith, Lane (New York, 2001)
A transmission received from outer space in a combination of different Earth languages tells of an alien schoolboy's fantastic excuse for being late to school again.
Keywords: Life on other planets; Fiction; Schools; Fiction